2014
DOI: 10.1590/1516-3180.2014.1322640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Candida albicans and non-albicans isolates from vaginal secretions: comparative evaluation of colonization, vaginal candidiasis and recurrent vaginal candidiasis in diabetic and non-diabetic women

Abstract: CONTEXT AND OBJECTIVE: Vulvovaginal candidiasis (VVC) is caused by abnormal growth of yeast-like fungi on the female genital tract mucosa. Patients with diabetes mellitus (DM) are more susceptible to fungal infections, including those caused by species of Candida. The present study investigated the frequency of total isolation of vaginal Candida spp., and its different clinical profiles -colonization, VVC and recurrent VVC (RVVC) -in women with DM type 2, compared with non-diabetic women. The cure rate using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
2
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 13 publications
3
51
2
7
Order By: Relevance
“…We detected the yeast in 27% of the study population, corresponding to a prevalence of approximately 13% both for colonization and for vulvovaginal candidiasis. Similar and lower rates of fungal isolation in women with and without vulvovaginitis have been described in other studies of the southern region: 11 and 24.7% in patients in the state of Paraná,12, 13, 14, 15 23.8% in patients in the state of Santa Catarina 12 and 18.2% in the city of Santo Ângelo-RS, 16 the latter being the only study held in Rio Grande do Sul. These differences in the isolation of Candida spp.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We detected the yeast in 27% of the study population, corresponding to a prevalence of approximately 13% both for colonization and for vulvovaginal candidiasis. Similar and lower rates of fungal isolation in women with and without vulvovaginitis have been described in other studies of the southern region: 11 and 24.7% in patients in the state of Paraná,12, 13, 14, 15 23.8% in patients in the state of Santa Catarina 12 and 18.2% in the city of Santo Ângelo-RS, 16 the latter being the only study held in Rio Grande do Sul. These differences in the isolation of Candida spp.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, C. albicans was predominant, accounting for over 60% of the isolates both in colonized patients and in those with VVC. In fact, this species is the most pathogenic of the gender, being related to most cases of VVC described, and generally represents more than half of the isolates identified in other studies 7, 15, 16, 22. Ferraza and co-workers 12 described the identification of this species in Santa Catarina in 100% and 72% of isolates from the asymptomatic and symptomatic patients, respectively, and in 66.7% of patients with VVC in state of Paraná.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Outros estudiosos abordam o DM como fator predisponente para aquisição de CVV (GUNTHER et al, 2014). Sendo assim, se as causas e as consequências são conhecidas, a prevenção se torna eficaz e satisfatória.…”
Section: Discussionunclassified
“…Alves et al (2014) demonstrated that progesterone might have a major influence on C. albicans pathogenicity on vaginal epithelial cells, which may partly explain the changes in susceptibility of women to vulvovaginal candidiasis (VVC) at different stages of the menstrual cycle. Gunther et al (2014) reported that diabetes mellitus type 2 was associated with yeast colonization, VVC and recurrent VVC in Brazilian women.…”
Section: Discussionmentioning
confidence: 99%